HUBUNGAN ANTARA PERILAKU IBU DAN KEJADIAN DIARE PADA BAYI DI WILAYAH KERJA PUSKESMAS SIANTAN HILIR - ., Nimas Prita R K W (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Diarrhea refers to discharging feces more than three times aday with aqueous constitution. Diarrhea is the second major cause ofdeath on infant globally and a leading cause of mortality and morbidity oninfant in Indonesia. Diarrhea can cause inadequate dietary intake and canbe attributed to growth failure during early childhood. Diarrhea isinfluenced by some risk factor, especially mother’s behavior. Objective.To know a correlation between mother’s behavior and prevalence ofdiarrhea on infant in working area of Siantan Hilir public health service.Method. This research method was analytic with a sample size of 76mothers of infant. Data were collected by face-to-face interviews. To getthe sample used simple random sampling. Result. The majority ofrespondents have moderate level of knowledge (47,4%). Most of attitudelevel of respondents are good attitude category (76,3%). Most of practicelevel of respondents are good practice category (73,7%). There was asignificant correlation between mother’s level of knowledge andprevalence of diarrhea on infant with p value = 0,004. There was asignificant correlation between mother’s level of attitude and prevalence ofdiarrhea on infant with p value = 0,003. There was a significant correlationbetween mother’s level of practice and prevalence of diarrhea on infantwith p value = 0,000. Conclusion. It is concluded that there was asignificant correlation between mother’s behavior and prevalence ofdiarrhea on infant. Suggestion. Information about diarrhea need frequentcontinuously to improving people healthy behavior.Keyword: Diarrhea, Behavior, Knowledge, Attitude, Practice 1) Medical Faculty, Tanjungpura University, Pontianak, West Borneo2) Department of Health Community, Medical Faculty, Tanjungpura University, Pontianak, West Borneo3) Department of Parasitology, Medical Faculty, Tanjungpura University, Pontianak, West Borneo